Proceedings of the 2013 International Conference on Education, Management and Social Science 2013
DOI: 10.2991/icemss.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Research on Construction of the Chinese University Internal Control system

Abstract: With the deepening of education system and the college expansion plan in China, universities have witnessed great changes in personnel training, capital source, funds management and performance evaluation. However, the current system of internal control in universities fails to match to these new trends which cannot adapt to these new needs of fostering talents, scientific research and serving for society to some extent. Thus, how to improve the theory and practice of the system of internal control in universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Yu haopeng (2012) analyzed the constraints of raising construction by using the optimality theory, and pointed out that the generation of Chinese raising construction depends on whether the input argument has topic characteristics, but he did not explain the motivation or process of raising construction [6,7]. Wang Min (2008), He Yi (2008), Wu Yimin and Lv Luodan (2010), and He Wei (2012/2013) indicated that after the abandonment of the Government and Binding Theory, the Extended Projection Principle (EPP) can explain the generation process of Chinese raising construction, which satisfies the framework of the Minimalist Program [8][9][10][11][12]. However, as Liang Jing (2020) pointed out, although the EPP can explain some sentences of Chinese raising construction, it has not explained more complex changes in Chinese raising construction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Yu haopeng (2012) analyzed the constraints of raising construction by using the optimality theory, and pointed out that the generation of Chinese raising construction depends on whether the input argument has topic characteristics, but he did not explain the motivation or process of raising construction [6,7]. Wang Min (2008), He Yi (2008), Wu Yimin and Lv Luodan (2010), and He Wei (2012/2013) indicated that after the abandonment of the Government and Binding Theory, the Extended Projection Principle (EPP) can explain the generation process of Chinese raising construction, which satisfies the framework of the Minimalist Program [8][9][10][11][12]. However, as Liang Jing (2020) pointed out, although the EPP can explain some sentences of Chinese raising construction, it has not explained more complex changes in Chinese raising construction [13].…”
Section: Introductionmentioning
confidence: 99%
“…The operation modes of space payload are much more complex, as the system size becomes larger [1]. It can be identified by the telemetry data related to the payload in orbit.…”
Section: Introductionmentioning
confidence: 99%